1991
DOI: 10.1037/0735-7028.22.3.247
|View full text |Cite
|
Sign up to set email alerts
|

Psychological test usage with adolescent clients: 1990 survey findings.

Abstract: Despite increasing interest in the psychological assessment of adolescents, no test usage surveys have specifically targeted practitioners who work with teenagers. This study involved distribution of research surveys to 600 psychologists; the 165 respondents who provided usable data yielded an adjusted response rate of 36%. The Wechsler Intelligence Scales, the Rorschach, and the Minnesota Multiphasic Personality Inventory (MMPI) were identified as the most widely used intellectual, projective, and objective i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
80
0
3

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(87 citation statements)
references
References 14 publications
4
80
0
3
Order By: Relevance
“…One of the most commonly given tests to assist in determining mental problems is the Rorschach (Archer, Maruish, Imhof, & Piotrowski, 1991). The purpose of this study is to determine whether specific variables on the Rorschach correspond to DSM-IV criteria and whether there are significant differences between children and adolescents with Asperger's Disorder and those with other behavioral and emotional problems on those same variables.…”
Section: Dsm-iv Criteria and Rorschach Variablesmentioning
confidence: 99%
“…One of the most commonly given tests to assist in determining mental problems is the Rorschach (Archer, Maruish, Imhof, & Piotrowski, 1991). The purpose of this study is to determine whether specific variables on the Rorschach correspond to DSM-IV criteria and whether there are significant differences between children and adolescents with Asperger's Disorder and those with other behavioral and emotional problems on those same variables.…”
Section: Dsm-iv Criteria and Rorschach Variablesmentioning
confidence: 99%
“…Studies of test usage with different groups of mental health professionals across many years have consistently found drawings to be among the top ten most frequently used assessment tools (Archer et al, 1991;Camara et al, 2000;Cashel, 2002;Kennedy et al, 1994;Lubin et al,1985;Watkins et al, 1995). These findings are especially interesting since the research regarding the validity of projective drawings in assessment has been mixed and concerns about their value as an assessment tool exist.…”
Section: Discussionmentioning
confidence: 79%
“…One recent survey, however, did focus on assessment with adolescent clients (Archer, Maruish, Imhof, & Piotrowski, 1991) and found that Human Figure Drawings (HFD), HTP, and Kinetic Family Drawing (KFD) were among the 10 most frequently used instruments. Studies of test usage by school psychologists have also indicated that projective drawings are commonly used in school settings .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Los tests del dibujo de la figura humana como una medida de la habilidad intelectual han sido algunos de los instrumentos psicológicos más utilizados en la práctica clínica y educativa infantil y adolescente (Archer, Maruish, Imhof & Piotrowski, 1991;Cashel, 2002;Costenbader, Rohrer & Difonzo, 2000;Flanagan & Motta, 2007). Este amplio uso se debe fundamentalmente a que la tarea que se propone es una actividad natural en la infancia, por lo que resulta atractiva y no ame nazante para los niños, y a que su carác-ter no verbal y breve permite la evaluación de niños con problemas de lenguaje, hiperactividad, atención y aprendizaje (Abell, Wood & Liebman, 2001;Scott, 1981) o que no hablan la lengua del país (Abell et al, 2001).…”
Section: Introductionunclassified